THE WORD ONE IN ENGLISH AND ITS EQUIVALENT IN INDONESIAN WITH REFERENCE TO ” THE DA VINCI CODE” - Hariawati, Ni Nyoman; Artawa, I Ketut; Udayana, I Nyoman (S2 Ilmu Linguistik Fakultas Ilmu Budaya Universitas Udayana, 2017)
AbstractThis research is conducting the word one in english and its equivalent in Indonesian with reference to the novel The Da Vinci Code, 2003 by Brown and its translation, 2013 by Dwijati. The word one in english has catagorized different part namely with singular by one , with plural by ones , modified with article- the, and determiner -that or -this. The catagorized of one could be found in the nominal substitution as cohesive device.The translation one in the English into Indonesian has correspodence equivalent in the text. Molina and Albier (2002:509) stated that translation techniques have five basic characteristics: they affect the result of the translation, they are classified by the comparison with the original, they affect micro-units of text, they are by nature discursive and contextual, and they are functional. The result of translation is made the equivalent between source language and targetlanguage. Based on equivalent Halliday (1976: 38) stated one as substitution is as the replacement of one item by another such as words or phrases. In line with Halliday, Renkema (1993: 38) stated that substitution is a replacement of a word (group) or sentence segment by a “dummy” word.The result in this research devided one into some types nominal substitution as one, ones, the one, this one and that one. The result of translation one can be function as nominal substitution and it?s equivalent in Indonesian.